Preparation and properties of calcium citrate nanosheets for bone graft substitute. Issue 5 (2nd September 2016) - Li, Junfeng; Liu, Yuqing; Gao, Yang; Zhong, Liangzhao; Zou, Qin; Lai, Xuefei
ABSTRACT: A convenient and effective soft chemical method is presented for the synthesis of nano-scaled calcium citrate sheets. The preparation involved the precipitation of nano-calcium citrate by adding ethanol to reach the super saturation state of a solution containing calcium and citrate salts. The obtained nano-calcium citrate formed nanosheets, with the following dimensions: width of about 50∼500 nm and thickness of about 8∼30 nm. The results of the XRD analysis confirmed that the obtained sample is calcium citrate tetrahydrate, and the crystal degree decreased with an increase quantity of ethanol added. Animal experiments showed that the calcium citrate can promote the formation of new bone.